Triple-Valued Neutrosophic Off for Public Digital Cultural Service Level Evaluation in Craft and Art Museums - Jiarong Jia (Neutrosophic Sets and Systems)
In the digital era, craft and art museums are increasingly leveraging technology to expand access to cultural heritage and engage broader audiences. The transformation of public cultural services into digital platforms raises critical questions about service quality, inclusiveness, and educational value. This study proposes a comprehensive evaluation framework for assessing the service level of public digital cultural offerings in craft and art museums. Six key criteria—digital accessibility, content richness, user engagement, usability, educational integration, and cultural outreach—form the basis for evaluating seven digital service alternatives. Using a neutrosophic set approach, this research analyzes the effectiveness and impact of each alternative on enhancing public interaction with cultural content. We use the Triple-Valued Neutrosophic Off (TVNOs) to overcome uncertainty and vague information. We show definitions and operations of TVNOs. The results demonstrate that immersive technologies, interactive tools, and education-oriented digital platforms significantly contribute to higher service quality. The findings offer valuable insights for cultural institutions seeking to design or refine their digital strategies for greater societal benefit.